What Farm Size Sustains a Living? Exploring Future Options to Attain a Living Income From Smallholder Farming in the East African Highlands - Marinus, Wytze; Thuijsman, Eva S.; van Wijk, Mark T.; Descheemaeker, Katrien; van de Ven, Gerrie W. J.; Vanlauwe, Bernard; Giller, Ken E. (Frontiers in Sustainable Food Systems, 2022)
Smallholder farming in sub-Saharan Africa keeps many rural households trapped in a cycle of poor productivity and low incomes. Two options to reach a decent income include intensification of production and expansion of farm areas per household. In this study, we explore what is a ‘viable farm size’, i.e. the farm area that is required to attain a ‘living income’, which sustains a nutritious diet, housing, education and health care. We used survey data from three contrasting sites in the East African highlands—Nyando (Kenya), Rakai (Uganda) and Lushoto (Tanzania) to explore viable farm sizes in six scenarios. Starting from the baseline cropping system, we built scenarios by incrementally including intensified and re-configured cropping systems, income from livestock and off-farm sources. In the most conservative scenario (baseline cropping patterns and yields, minus basic input costs), viable farm areas were 3.6, 2.4 and 2.1 ha, for Nyando, Rakai and Lushoto respectively—while current median farm areas were just 0.8, 1.8 and 0.8 ha. Given the uneven distribution of current farm areas, only few of the households in the study sites (0%, 27% and 4% for Nyando, Rakai and Lushoto respectively) were able to attain a living income. Intensification of production from baseline yields to 50% of the water-limited yields strongly decreased the viable farm size, and thereby enabled 92% of the households in Rakai and 70% of the households in Lushoto to attain a living income with their current farm area. For Nyando however, intensification of crop production alone was not enough, but including income from livestock enabled the majority of households (73%) to attain a living income on their current farm areas. Our scenarios showed that increasing farm area and/or intensifying production is required for smallholder farmers to attain a living income from farming. However, such changes require considerable capital and labour investment, and possibly land reforms. Hence, smallholders would require support (e.g. input subsidies), protection (e.g. secure land access, price protection) and alternative off-farm employment options. Integrated policy is therefore imperative for all to attain a decent living.